2010
DOI: 10.1017/s1751731110001187
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin A supplementation at different gaseous environments on in vitro development of pre-implantation sheep embryos to the blastocyst stage

Abstract: Vitamin A (all-trans retinol) is an important antioxidant whose role in embryo development in vitro and in vivo is well established. Oxidative stress is a major cause of defective embryo development. This study evaluated the effects of all-trans retinol supplementation to maturation and embryo culture media under different gaseous environments on the development of ovine oocytes and embryos in vitro. The percentages of cleavage, morula and blastocyst, total cell count and comet assay were taken as indicators o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
(38 reference statements)
1
9
0
Order By: Relevance
“…The natural metabolites of retinol (RT) such as all- trans retinoic acid (t-RA) and 9- cis RA are collectively known as retinoids and are considered as non-enzymatic antioxidants (Guerin et al , 2001). Recent protocols have used these compounds in the culture medium of embryos taking into account their deep effect upon cellular survival, proliferation, differentiation and embryonic morphogenesis (Noy, 2010; Rajesh et al , 2010; Rhinn & Dollé, 2012; Conceição et al , 2015; Conceição et al , 2016). It was found that the addition of retinoids to the culture medium enhances the subsequent preimplantation embryonic development in bovine embryos (Lima et al , 2004; Ahmed et al , 2016), and in goat embryos (Duque et al , 2002a,b; Lima et al , 2006; Chiamenti et al , 2010, 2012; Conceição et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The natural metabolites of retinol (RT) such as all- trans retinoic acid (t-RA) and 9- cis RA are collectively known as retinoids and are considered as non-enzymatic antioxidants (Guerin et al , 2001). Recent protocols have used these compounds in the culture medium of embryos taking into account their deep effect upon cellular survival, proliferation, differentiation and embryonic morphogenesis (Noy, 2010; Rajesh et al , 2010; Rhinn & Dollé, 2012; Conceição et al , 2015; Conceição et al , 2016). It was found that the addition of retinoids to the culture medium enhances the subsequent preimplantation embryonic development in bovine embryos (Lima et al , 2004; Ahmed et al , 2016), and in goat embryos (Duque et al , 2002a,b; Lima et al , 2006; Chiamenti et al , 2010, 2012; Conceição et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We selected 14 studies using the comet assay on animal embryos matching our criteria, out of 118 studies retrieved. In these studies, fresh embryos were all obtained by natural mating (Fabian et al, 2003;Harrouk et al, 2000;Müller et al, 1996;Takahashi et al, 1999;Tranguch et al, 2003;Webster et al, 2000) or IVF (Hwang et al, 2013;Ju et al, 2010;Kitagawa et al, 2004;Natarajan et al, 2010;Rajesh et al, 2010;Sturmey et al, 2009;Takahashi et al, 2000;Valivittan, 2009a, 2009b). This review of the literature shows that there is no standardization of the protocol: Seven different animal species were used; The ZP was removed in 4 studies; The protocols for the transfer of the embryos in the LMP agarose layer were heterogeneous: a minimum of half a blastocyst and a maximum of 20 cleavage embryos were transferred, and the volume of LMP varied from 4 μL to 50 μL; The lysis and electrophoresis protocols were also heterogeneous.…”
Section: Embryo Viability and Culture Conditionsmentioning
confidence: 99%
“…All of the published comet assay protocols on mice embryos (Fabian et al, 2003;Harrouk et al, 2000;Hwang et al, 2013;Kitagawa et al, 2004;Müller et al, 1996;Natarajan et al, 2010;Rajesh et al, 2010;Sturmey et al, 2009;Takahashi et al, 1999Takahashi et al, , 2000Valivittan, 2009a, 2009b;Tranguch et al, 2003;Webster et al, 2000) used 2 layers of agarose except one (Ju et al, 2010). A glass microscope slide is initially coated with 1% high or normal-melting point (HMP, NMP) agarose (the first agarose layer), and then, the embryos are mixed with a drop of low-melting point (LMP) agarose and placed on the first layer (the second agarose layer).…”
Section: Embryo Viability and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover this reproductive biotechnology has enabled large amounts embryo production of superior breeds in various domestic animals and the production of large numbers of embryos for scientific research purposes from slaughtered and/ or live animals [2,3] . Production of embryos in vitro also has potential for revolutionizing in cattle breeding and husbandry around the globe.…”
Section: Introductionmentioning
confidence: 99%